Epinephrine: A Review of Current Understanding and Future Direction - Ketchem, Justin; Ketchem, Elizabeth; Mishra, Samarth; Kapuria, Rohan; Majeed, Ban; Walsh, David; Islam, K.M. (International Journal of Innovative Research in Medical Science, 2024)
Introduction: The administration of injectable epinephrine is a widely utilized mechanism which has been employed as a lifesaving medication for decades. Despite the prevalence of this treatment technique, certain situations and patient populations necessitate a replacement for the epinephrine auto injector (EAI). There are several disadvantages of traditional EAIs. These drawbacks include high cost, short shelf life, low carry rate, difficulty to use or train with, fear of needles, fixed dosages, and fixed needle length. The most promising EAI alternatives include sublingual tablets and intranasal spray. These delivery methods have similar pharmacological effectiveness to EAIs with the benefits of modifiable dosages, high stability, and simplified administration. This review aims to evaluate deficiencies in implementation of the currently used EAI, investigate newly developed alternative delivery methods, identify gaps in the current literature, and suggest possible future studies.